Explanatory notes on key topics in the regulation of water and sanitation services - Groom, Eric (World Bank, 2006)
In the past few decades, water sector reforms worldwide have focused attention on economic regulation. These notes, financed by the Government of the Netherlands through the Bank-Netherlands Partnership Program (BNPP), provide a framework of steps for regulation of water supply services based on the premise that economic regulation monitors, enforces, and adjusts tariffs and service standards for water providers. While there is an overlap, the definition of economic regulation should be kept distinct from ownership, policy making and governance functions. Although the traditional form of regulation has been to prohibit monopolies from overcharging customers, the challenge in developing countries is to increase average prices that are too low. Charging below cost is meant to help consumers, but it is generally counterproductive because it forces the provider to rely on government subsidies or to cut back on service, maintenance, and investment. Regulation should be limited to making providers offer services at reasonable tariffs that cover the cost of providing the service, but no more. The paper also explores the regulation of privately-operated utility services and provides guidance on wastewater service regulation, which requires improving small-scale systems and central environmental regulation.